Punishment, probation and parole : mapping out 'mass supervision' in international contexts - Maier, Katharina; Ricciardelli, Rosemary; McNeill, Fergus (Emerald Publishing Limited, 2023)
In many countries, community-based penalties such as probation, electronic monitoring and parole are the most common sanctions used in the punishment of criminalized individuals. Despite the widespread use of community-based penalties, these forms of penalization or punishment remain a less studied feature of punishment research today. Punishment, Probation and Parole maps this lacuna in knowledge and scholarship while charting a path to fill it. Bringing together a series of key conceptual papers by leading scholars, the chapters explore the various dimensions and forms of community-based penalties as they are constructed and experienced in different times and places, producing different socio-penal effects. Addressing pressing debates and emerging concepts, this much-needed collection serves to chart directions for future researchers to explore in the field of community-based penalties.